Bootcamp Seminar and Machine Learning Algorithm Workshop for the Data Science Club - Agus Eko Minarno; Lailis Syafa’ah; Moch. Chamdani Mustaqim (Jurnal Dedikasi, 2021)
The development of data and information needs in the era of Society 5.0 is very crucial because it determines many business decisions. Data in the past becomes valuable when it becomes a historical fact that can illustrate findings to assess future business directions. Based at the University of Muhammadiyah Malang, the Data Science Club has a total membership of more than 200 people spread across East Java. The problem that often occurs in the Data Science community is Machine Learning algorithms' low literacy, especially for new members. Coupled with the development of the Machine Learning algorithm that is so fast and massive. For that, we need activities that can directly impact the Data Science community by presenting the latest algorithms and programming techniques. This service activity proposes a Machine Learning workshop for Data Science by teaching various computational algorithms to the Indonesian Data Science community, which has spread in Indonesia and the East Java region. This activity presents 12 workshop materials for participants who will be delivered by speakers who have expertise in their fields, both from the University of Muhammadiyah Malang, and present national speakers in collaboration with the Data Science Club of the University of Muhammadiyah Malang.